Metal-oxide phase transition of platinum nanocatalyst below fuel cell open-circuit voltage - Carlos A. Campos-Roldán; Amir Gasmi; Meryem Ennaji; Morgane Stodel; Isaac Martens; Jean-Sébastien Filhol; Pierre-Yves Blanchard; Sara Cavaliere; Deborah Jones; Jakub Drnec; Raphaël Chattot (Nature Communications)
Abstract The long-term stability of Pt-based catalysts is critical to the reliability of proton exchange membrane fuel cells (PEMFCs), and receives constant attention. However, the current knowledge of Pt oxidation is restricted to unrealistic PEMFC cathode environment or operation, which questions its practical relevance. Herein, Pt oxidation is investigated directly in a PEMFC with stroboscopic operando high energy X-ray scattering. The onset potential for phase transition of the nanoparticles surface from metallic to amorphous electrochemical oxide is observed far below previously reported values, and most importantly, below the open-circuit potential of PEMFC cathode. Such phase transition is shown to impact PEMFC performance and its role on Pt transient dissolution is verified by electrochemical on-line inductively coupled plasma mass spectrometry. By further demonstrating and resolving the limitations of currently employed accelerated stress test protocols in the light of metal-oxide phase transitions kinetics, this picture of Pt oxidation enables new mitigation strategies against PEMFC degradation.